MORPHOLOGICAL AND PHYSIOLOGICAL RESPONSES OF DIFFERENT COTTON GENOTYPES UNDER NORMAL AND SALT STRESS CONDITIONS - RAFIQUE, M; NISA, A; MUNSHA, A; BATOOL, Z; ASLAM, I; FAHEEM, J; NOFAL, M; IMRAN, M; ALI, S; REHMAN, A (Biological and Clinical Sciences Research Journal, 2024)
Salinity is a major abiotic stress that badly affects the growth and production of cotton worldwide. This scenario is not different in the case of Pakistan. This research was conducted to examine the effects of different salinity levels on the morpho-physiological characters of six cotton genotypes i.e. shoot and root length, fresh shoot and root weight, photosynthesis rate, and transpiration rate. A pot experiment was arranged with three salinity treatments of NaCl i.e. control (0 dS/m), T1 (4.5 dS/m), and T2 (8.5 dS/m) with three replications of each treatment. Highly significant decreases in shoot length, fresh shoot weight, fresh root weight, photosynthesis rate, and transpiration rate were observed with increasing salinity levels across all genotypes. The genotype MNH-786 showed the highest reduction in all morpho-physiological characters, indicating it was highly sensitive to salinity stress. On the other hand, FH-87 and FH-142 maintained relative performance for all discussed morpho-physiological traits under both moderate and high salinity, demonstrating that these are relatively more tolerant. These findings provided valuable insights into the salinity tolerance of cotton genotypes and highlighted the potential of FH-87 and FH-142 for cultivation in saline-prone areas and for use in breeding programs to improve salinity tolerance in cotton.